Aux marges de la cité : l'exclusion sociale et professionnelle en France (xvie-xixe siècle) - Bourdin, Philippe (Actes des congrès nationaux des sociétés historiques et scientifiques, 2023)
Between the 16th and 19th centuries, France offered us a multifaceted mirror of marginality. Whether the approach is economic, religious, political or cultural, we are brought back to the difficult relationship with otherness constructed by a univocal model of power, an absolute monarchy or empires that married the throne and the altar, around a king or a war emperor. The aim of the contributions in this collection is to reflect on the way in which these banishments have constructed the figure of the other, the foreigner, within his own country of origin or host country, or have defined civil and civic rights that are indissolubly linked to a community of destinies, thoughts and interests. However, none of the marginalisation and suffering imposed is without resistance, without stubborn and protracted struggles for recognition, for individual and collective freedoms, for equal rights, as current events never deny.